Acute compartment syndrome following cardiovascular surgery: a rare and catastrophic complication highlighting the importance of early detection and intervention - Xianwen Hu; Youjun Pan; Zhiru Che; Yingya Cao; Xiaogan Jiang; Qiancheng Xu; Weihua Lu (BMC Cardiovascular Disorders)
Abstract Background Acute compartment syndrome (ACS) is a critical condition resulting from increased intra-compartmental pressure, causing tissue ischemia and necrosis. ACS following cardiovascular surgery is rare but catastrophic. Postoperative sedation and analgesia often obscure classic symptoms, delaying diagnosis. This underscores the importance of vigilance and early detection, particularly in high-risk scenarios such as prolonged extracorporeal circulation and femoral artery cannulation. Enhanced monitoring, including tissue oxygen saturation and transcutaneous oxygen pressure, may facilitate timely diagnosis. Case summary We report a 56-year-old male who developed ACS after valve replacement surgery involving femoral artery cannulation for cardiopulmonary bypass. Approximately 12 h postoperatively, the patient exhibited severe lower limb swelling, mottling, and diminished dorsalis pedis pulse. Laboratory findings revealed elevated myoglobin and creatine kinase levels. Diagnosis was confirmed via clinical and ultrasound evaluation, prompting emergent fasciotomy. Postoperative management included wound care, renal replacement therapy, and skin flap reconstruction. At 6 months follow-up, the patient achieved complete functional recovery of the affected limb. Conclusion ACS is a rare but severe complication of cardiovascular surgery. This case highlights the necessity for heightened vigilance, early recognition, and timely intervention to mitigate adverse outcomes. Further studies are needed to validate and establish standardized monitoring protocols and management strategies, including early use of distal perfusion techniques, to improve surgical safety and patient outcomes.